Frequency of Gall Stones in Patients with Acute Pancreatitis on Ultrasound - Aanab Hayat, Abbas Ahmad, Muhammad Sohail Khan, Inamullah, Saira Khan, Asif Iqbal, (Pakistan Journal of Medical & Health Sciences, 2024)
Purpose: The aim of the study was to identify the preponderance of the incidence of gallstones in a tertiary care hospital on ultrasonography regarding gallstones in patients with acute pancreatitis. Methods: The study period was from 16 October, 2020 to 16 April, 2021, and the Department of Radiology at Hayatabad Medical Complex was selected as the study setting. One hundred and sixty-five patients between 18 and 60 years old who had presented within 48 hours after the onset of symptoms and met the operational definition of acute pancreatitis were recruited via non-probability consecutive sampling. Ultrasound was used to evaluate visualisation of gallstones on the basis of standard grey-scale criteria with posterior acoustic shadowing and positional mobility, and Doppler where possible. SPSS version 23 was used to analyse data. Quantitative variables were reported as mean ± SD, and categorical variables as frequencies/percentages. Age group, gender, and BMI were stratified by gallstone status, and the chi-square test was used (p<0.05). Findings: The average age was 42.000 12.88; 57 per cent of the participants were men. Mean BMI was 26 ± 3.39 kg/m². The prevalence of gallstones was 68 (41) patients. There was no significant correlation with age (p=0.9790), gender (p=0.9336) and BMI (p=0.9394). Conclusion: 41% of patients with acute pancreatitis had gallstones on ultrasound and this evidence aligned with the need to conduct early biliary imaging as a routine procedure in this environment. Keywords: Acute pancreatitis; Gallstones; Ultrasonography; Biliary pancreatitis; Frequency; Hayatabad Medical Complex; Pakistan